Associations among Dietary Omega-3 Polyunsaturated Fatty Acids, the Gut Microbiota, and Intestinal Immunity. (4th January 2021) - Fu, Yawei; Wang, Yadong; Gao, Hu; Li, DongHua; Jiang, RuiRui; Ge, Lingrui; Tong, Chao; Xu, Kang
Abstract : Omega-3 polyunsaturated fatty acids (omega-3 PUFAs), which are essential fatty acids that humans should obtain from diet, have potential benefits for human health. In addition to altering the structure and function of cell membranes, omega-3 PUFAs (docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), alpha-linolenic acid (ALA), and docosapentaenoic acid (DPA)) exert different effects on intestinal immune tolerance and gut microbiota maintenance. Firstly, we review the effect of omega-3 PUFAs on gut microbiota. And the effects of omega-3 PUFAs on intestinal immunity and inflammation were described. Furthermore, the important roles of omega-3 PUFAs in maintaining the balance between gut immunity and the gut microbiota were discussed. Additional factors, such as obesity and diseases (NAFLD, gastrointestinal malignancies or cancer, bacterial and viral infections), which are associated with variability in omega-3 PUFA metabolism, can influence omega-3 PUFAs–microbiome–immune system interactions in the intestinal tract and also play roles in regulating gut immunity. This review identifies several pathways by which the microbiota modulates the gut immune system through omega-3 PUFAs. Omega-3 supplementation can be targeted to specific pathways to prevent and alleviate intestinal diseases, which may help researchers identify innovative diagnostic methods.